2016
DOI: 10.1155/2016/2742648
|View full text |Cite
|
Sign up to set email alerts
|

Previously Unidentified Single Nucleotide Polymorphisms in HIV/AIDS Cases Associate with Clinical Parameters and Disease Progression

Abstract: The genetic background of an individual plays an important role in the progression of HIV infection to AIDS. Identifying previously unknown or uncharacterized single nucleotide polymorphisms (SNPs) that associate with disease progression may reveal important therapeutic targets and provide a greater understanding of disease pathogenesis. In the present study, we employed ultra-high multiplex PCR on an Ion Torrent next-generation sequencing platform to sequence 23 innate immune genes from 94 individuals with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…[ 52 ] In an Omani cohort, [ 55 ] the relationship between TLR4 (1063A/G, 1363C/T) gene polymorphism and the CD4 and CD8 cell counts and viral load was not found. In the studies of TLR7 gene polymorphisms, Oh et al [ 44 ] showed TLR 7 rs179008 is associated high viral loads and lower baseline CD4 T-cell counts, which was consistent with Anokhin et al, [ 56 ] but inconsistent with Said et al [ 57 ] TLR8 rs3764880 was conferred a significantly protective effect regarding progression of the disease. [ 45 ] The results reporting of the influence of the TLR9 rs352140 on disease progression are contradictory.…”
Section: Resultsmentioning
confidence: 82%
“…[ 52 ] In an Omani cohort, [ 55 ] the relationship between TLR4 (1063A/G, 1363C/T) gene polymorphism and the CD4 and CD8 cell counts and viral load was not found. In the studies of TLR7 gene polymorphisms, Oh et al [ 44 ] showed TLR 7 rs179008 is associated high viral loads and lower baseline CD4 T-cell counts, which was consistent with Anokhin et al, [ 56 ] but inconsistent with Said et al [ 57 ] TLR8 rs3764880 was conferred a significantly protective effect regarding progression of the disease. [ 45 ] The results reporting of the influence of the TLR9 rs352140 on disease progression are contradictory.…”
Section: Resultsmentioning
confidence: 82%
“…Genome-wide association studies (GWAS) is a powerful approach to unravel the genetics behind complex diseases [59]. In HIV research, GWAS has identified a number of SNPs associated with different forms of HIV progression [60]. The first GWAS in the HIV context was in the HLA class I locus that confirmed a major effect of HLA-B*57 in reducing viral load [61].…”
Section: Discussionmentioning
confidence: 99%
“…OAS2 and OAS3) [109]. In contrast, other SNPs identified in OAS2 and OAS3 genes and in the TRIM5 gene were associated with a slower progression of disease [109]. Several studies have reported controversial results on the influence of retroviral restriction factor SNPs (e.g.…”
Section: Host Factorsmentioning
confidence: 99%
“…Additionally, SNPs associated with progression from HIV-1 infection to AIDS were identified in two 2′-5′-OAS genes (e.g. OAS2 and OAS3) [109]. In contrast, other SNPs identified in OAS2 and OAS3 genes and in the TRIM5 gene were associated with a slower progression of disease [109].…”
Section: Host Factorsmentioning
confidence: 99%
See 1 more Smart Citation